The impact of a liberalisation law on legally induced abortion hospitalisations. (August 2016) - Gonçalves-Pinho, Manuel; Santos, João V.; Costa, Antónia; Costa-Pereira, Altamiro; Freitas, Alberto
Abstract: Objectives: Legal abortion based purely in maternal option without fetal/maternal pathology was liberalised in Portugal in 2007 and since then abortion rates have increased substantially. The aim of this paper was to study the impact of the liberalisation of abortion by maternal request on total legal abortion related hospitalisation trends. Study design: We considered hospitalisations of legal abortion (ICD-9-CM codes 635.x) with discharges from 2000 to 2014. Data was obtained from a Portuguese administrative database, which contains all registered public hospitalisations in mainland Portugal. Performed legal abortions during the same period were obtained from INE (National Statistics Institute). Hospitalisations per abortion were calculated by dividing the number of legal abortions hospitalisations per the number of legal abortions, mean ages, number of hospitalisations per age group, complications, admission type and length of stay were also analysed, throughout the study period. Results: Hospitalisations rose during the study period, (from 618 episodes in 2000 to 1, 259 in 2014, with a peak of 1, 603 in 2010). Since the liberalisation law was passed there was a significant decrease in the number of hospitalisations per abortion: from 1.07 in 2000 to 0.11 in 2014 ( p  < 0.001). Furthermore, the mean age maintained stable since liberalisation (30.8 years before 2007 and 31.0 after). Abortion related hospitalisations are more frequent in women aged 25–39. A significant decrease from the emergent to the scheduled type of admission occurred from 2000 to 2014 (from 83.5% to 56.7% of emergent admissions) ( p  < 0.001). Complications remained stable between 2000 and 2014 and delayed or excessive haemorrhage was the most frequent (4.6%). Conclusions: Since the liberalisation, hospitalisations per abortion have decreased, reflecting the major impact that the liberalisation of legal abortion by maternal request had on abortion trends nationwide. Before the liberalisation, each abortion led to approximately one hospitalisation while after the liberalisation this trend shifted to approximately 10% of the number of abortions. Legal abortion related hospitalisations are more frequent in women aged between 25 and 39 years old, an older age group when compared to the one registered in all cases of legal abortions, reflecting the differences between those hospitalised and those who are not. Our study shows the impact that legal abortion by maternal request liberalisation law can bring to abortion and to hospitalisation trends.